2016
DOI: 10.3390/rs8010075
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ASTER-Like Daily Land Surface Temperature by Fusing ASTER and MODIS Data during the HiWATER-MUSOEXE

Abstract: Land surface temperature (LST) is an important parameter that is highly responsive to surface energy fluxes and has become valuable to many disciplines. However, it is difficult to acquire satellite LSTs with both high spatial and temporal resolutions due to tradeoffs between them. Thus, various algorithms/models have been developed to enhance the spatial or the temporal resolution of thermal infrared (TIR) data or LST, but rarely both. The Spatial and Temporal Adaptive Reflectance Fusion Model (STARFM) is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…The RMSEs (MAEs) for spring maize and sunflower were 1.47 (1.17 K) and 0.73 K (0.5 K), respectively. The overall discrepancy is close to what has been presented by G. Yang et al () with the RMSE ranging from 1.09 to 1.31 K, and the MAE from 1.41 to 1.72 K. The scatter points between the measured LST and the downscaled LST E are generally close to the 1:1 line (Figure ), with R 2 values of 0.83 and 0.92 for spring maize and sunflower, indicating the good performance of the downscaled LST E estimates. For spring wheat, the LST measurements were higher than the downscaled LST E estimates with the RMSE, MAE, and R 2 of 2.75 K, 2.56 K, and 0.55, respectively.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The RMSEs (MAEs) for spring maize and sunflower were 1.47 (1.17 K) and 0.73 K (0.5 K), respectively. The overall discrepancy is close to what has been presented by G. Yang et al () with the RMSE ranging from 1.09 to 1.31 K, and the MAE from 1.41 to 1.72 K. The scatter points between the measured LST and the downscaled LST E are generally close to the 1:1 line (Figure ), with R 2 values of 0.83 and 0.92 for spring maize and sunflower, indicating the good performance of the downscaled LST E estimates. For spring wheat, the LST measurements were higher than the downscaled LST E estimates with the RMSE, MAE, and R 2 of 2.75 K, 2.56 K, and 0.55, respectively.…”
Section: Resultssupporting
confidence: 87%
“…Weng et al () modified the STARFM algorithm and proposed the Spatiotemporal Adaptive Data Fusion Algorithm method to generate synthetic Landsat‐like daily thermal radiance and LST data by considering the annual temperature cycle. They found that the prediction accuracy for the whole study area ranged from 1.3 to 2.0 K. G. Yang et al () conducted a comprehensive evaluation of the ESTARFM algorithm for generating ASTER‐like daily LSTs by blending ASTER and MODIS images. The algorithm was also directly used to map daily ET at field scales and successfully achieved the data fusion products with root‐mean‐square error (RMSE) ranging from 1.11 to 1.81 mm/day (Bai et al, ; Cammalleri et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more impacting factors, including impervious surface fractions, water indices, and albedo, were considered. Until years after 2010, more proposal studies and application reports of thermal sharpening methods were found in literature [8,11,15,35,42,43]. However, it is found that for most of them, the scale factor (or zoom factor) of downscaling is still limited (<10) and the aiming sharpening resolutions, especially for applications of thermal sharpening data, are 1 km [15,44], 90 m [35], or 30 m [42], which are the spatial resolutions of MODIS, ASTER, and TM/ETM+, respectively.…”
Section: Application Of Thermal Sharpening For Urban Areamentioning
confidence: 99%
“…Voogt and Oke [34] have already criticized that the slow development of thermal remote sensing of urban areas is due largely to the qualitative description of thermal patterns. It is common to find in literature that, for comparison of LST spatial patterns or texture, people usually present a number of results in an illustration and then use a limited number of words for the description [35][36][37]. This revealed the lack of a widely acknowledged quantifying method for evaluation of the LST spatial pattern.…”
mentioning
confidence: 99%
“…Gao et al (2006) proposed a data fusion technique named the "spatial and temporal adaptive reflectance fusion model" (STARFM), that simultaneously integrates the temporal advantage of MODIS-like images and the spatial advantage of Landsat-like images [26]. This data fusion approach has lately received much attention, since it can provide high-resolution vegetation indices and land surface temperature estimates [27][28][29][30]. This approach additionally appears to hold great utility for high-resolution TIR data for ET mapping.…”
Section: Introductionmentioning
confidence: 99%